Mig-6 Gene Knockout Induces Neointimal Hyperplasia in the Vascular Smooth Muscle Cell - Ju Hee Lee (Disease Markers, 2014)
Although advances in vascular interventions can reduce the mortality associated with cardiovascular disease, neointimal hyperplasia remains a clinically significant obstacle limiting the success of current interventions. Identification of signaling pathways involved in migration and proliferation of vascular smooth muscle cells (SMCs) is an important approach for the development of modalities to combat this disease. Herein we investigate the role of an immediate early response gene, mitogen-inducible gene-6 (Mig-6), in the development of neointimal hyperplasia using vascular smooth muscle specific Mig-6 knockout mice. We induced endoluminal injury to one side of femoral artery by balloon dilatation in both Mig-6 knockout and control mice. Four weeks following injury, the artery of Mig-6 knockout mice demonstrated a 5.3-fold increase in the neointima/media ratio compared with control mice (P=0.04). In addition, Mig-6 knockout vascular SMCs displayed an increase in both cell migration and proliferation compared with wild-type SMCs. Taken together, our data suggest that Mig-6 plays a critical role in the development of atherosclerosis. This finding provides new insight into the development of more effective ways to treat and prevent neointimal hyperplasia, particularly in-stent restenosis after percutaneous vascular intervention.